Morpho-physiology and yield performance, and lea genes expression for drought tolerance of advanced mutant rice lines - Kamarudin, Zarith Shafika (2018)
Increasing genetic variability with mutagenic agents has been broadly employed in plant breeding because this method alters one or more desirable traits for an effective breeding programme. Based on this background, induced mutation was adopted to improve the popular Malaysian rice variety, MR219 for drought tolerance. The main objective of this study was to select the high-yielding drought-tolerant advanced mutant rice lines for commercial cultivation in Malaysia. The performance of selected mutant rice and check varieties were evaluated under different drought stress treatments for morphophysiological and biochemical characteristics, yield and yield components in glasshouse and field conditions. Glasshouse study showed that mutants MR219-4 and MR219-9 had significant higher yields compared to the check varieties when the plants were imposed with moderate and severe drought stresses at active tillering, booting and 50% flowering stages. Analysis of the drought tolerance indices indicated that the ability of drought tolerance for the MR219-4 and MR219-9 were different in response to each drought stress intensity. Based on stress tolerance level, stress tolerance index, stress susceptibility index and drought tolerance efficiency, MR219-4 was identified as drought-tolerant genotype with high yield under both drought conditions, moderate and severe, meanwhile MR219-9 was high-yielding drought-tolerant genotype only under moderate stress condition. Further experiment was carried out to evaluate the yield performances of these two advanced mutant rice lines under field drought stress condition at reproductive stage over two planting seasons. Study of drought stress under field condition showed MR219-4 was the best performance followed by MR219-9 under drought stress among all the rice genotypes for all the traits studied. These advanced mutant lines were selected as drought-tolerant genotype with high yield. LEA genes expression analysis was carried out on the selected rice genotypes to identify genes controlling the drought tolerance characteristic. The OsLEA1, OsLEA2, OsLEA3, OsLEA4 and OsLEA5 genes were found to be up-regulated with more than four-fold increase when exposed to drought stress treatment. The pattern of LEA expression in the MR219-4 and MR219-9 were highly similar with the drought-tolerant check variety (Aeron1) and therefore, MR219-4 and MR219-9 were confirmed as drought-tolerant mutant rice lines. These advanced mutant lines are highly recommended for large scale field evaluation in development of high-yielding drought-tolerant rice varieties.